2016
DOI: 10.3109/02713683.2016.1158272
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Propranolol in Retinopathy of Prematurity and its Correlation with the Platelet Mass Index

Abstract: In the study, it was found in the stage 2 ROP study group that propranolol reduced the need for laser photocoagulation significantly. Also, in parallel to the efficacy of propranolol in this study group, a decrease was observed in PMI values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
4
35
1
2
Order By: Relevance
“…In addition, it has been proposed that there is a relationship between the platelets' existing proinflammatory and anti-inflammatory effects and IVH that occurs in the brain of the immature newborn. 9,20,25 When considered with the above-mentioned data, the PMI values being detected low in SSG cases, in our study, corroborate the previous studies of its kind. Despite the presence of a multitude of studies in the literature that highlight similar mechanisms, the importance of oxygen use in terms of ROP, comprehensive studies on the relationship between oxygen use and IVH are rather limited.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, it has been proposed that there is a relationship between the platelets' existing proinflammatory and anti-inflammatory effects and IVH that occurs in the brain of the immature newborn. 9,20,25 When considered with the above-mentioned data, the PMI values being detected low in SSG cases, in our study, corroborate the previous studies of its kind. Despite the presence of a multitude of studies in the literature that highlight similar mechanisms, the importance of oxygen use in terms of ROP, comprehensive studies on the relationship between oxygen use and IVH are rather limited.…”
Section: Discussionsupporting
confidence: 92%
“…It is also known that platelets, apart from their effects on VEGF, contribute to the formation of new vascularizations by stimulating in vitro endothelial cells. 9,20,[25][26][27][28] The presence of the parallel relationship between the platelets playing crucial roles in the transport and storage of the factors involved in HIF and HIF-triggered angiogenesis factors is extremely important. Decrease in HIF levels causes the levels of platelet transported VEGF to drop, which can be interpreted to be the decrease in PMI as a laboratory finding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a pilot randomized controlled trial was performed (22) to verify the efficacy and safety of oral propranolol in preterm newborns with an advanced stage of ROP (stage 2 without plus in zone II) (23). Oral propranolol proved to be effective in reducing ROP progression, as also confirmed by other studies (24)(25)(26), and its possible role in ROP prevention is currently under investigation (Sanghvi KP, Singh U, manuscript in preparation).…”
supporting
confidence: 68%
“…Though the study of Bancalari et al 16 showed a decrease in the need for intervention with laser or bevacizumab in the study group, it was not a randomised controlled study. The study of Korkmaz et al 17 also showed a decrease in the need of laser photocoagulation in stage 2 ROP. In our study, though the incidence of plus disease decreased from 17.6% in the control group to 7.8% in the propranolol group, it failed to reach statistical significance, as our study was underpowered for this outcome.…”
Section: Discussionmentioning
confidence: 87%